Diálogo ética e saúde: formação profissional na perspectiva hermenêutica - Maraschin, Renata (2017)
The Health Human Resource Training goes through a process of theoretical, pedagogical and methodological reorientation since the National Curricular Guidelines and the Program of Reorientation of the Health Human Resource Training. This reorientation points to greater integration between teaching and service, having as core the expanded concept of health and ethic and solidarity professional work. The official documents guiding this change affirm that it will occur through the pedagogical proposal based on the pedagogy of the competences and active teaching-learning methodologies, understanding them as capable of leading the studentfuture professional to the ethical and solidary action. However, in this thesis, it is considered that such pedagogical proposal tends to be insufficient front of the health horizon. In front of this, it was analysed the contribution that can offers the concepts of dialogue, ethics and health, derived from the philosophical hermeneutics proposed by Hans-Georg Gadamer, to think The Health Human Resource Training in na enlarged way. It is a study of a bibliographical nature, guided by the hermeneutical posture in the work with the texts and other sources used. In order to respond to these purposes, the work is structured in three chapters. The first is based on the reading and problematization of the official documents that regules health graduations in Brazil, taken as the empirical basis on which the research is structured. By the examination of these documents was possible to identify, on the one hand, the existence of concern about the ethical dimension of training; on the other hand, the absence of greater conceptual clarification about the meaning of ethics adopted, even considering that health graduations are anchored in a pedagogical project centered on student learning and supported by the teacher as facilitator and mediator. The problematization carried out indicates that the absence of this greater conceptual clarification can lead to the understanding of ethics only as discourse, unrelated to the relationship between the living subjects involved in the formative process. It may lead to the emphasis of training remains on the technical-scientific perspective, a horizon that must be broaden and that focusing the pedagogical project on student learning does not favor a horizontalized, dialogical, cooperative, supportive and ethical educational relationship, once a central role is played only by one of the actors. As an alternative, it was proposed that the pedagogical model be centered on the relationship between teacher and student, in which the actors involved teach and learn simultaneously. In the second chapter, are rebuilt the general traces of Gadamer's hermeneutics and the concepts of dialogue, ethics and health derived from it. In the third chapter is made the conceptual work about the pedagogy of competences and active teachinglearning methodologies, investigating how the concepts of phronesis (ethical knowledge) and dialogue, because centered on the subject-subject relationship, can constitute an alternative to extend the presupposed of the subject-object relationship, basis on which the pedagogy of competences is structured. The results obtained allow to conclude that developing a pedagogical model in Health Human Resource Training anchored in hermeneutics may allow future professional action marked by interactions with the other (patient, user, community) more humanized because guided by the ethical perspective (subject-subject relationship ), without disregarding the relevance of the epistemological perspective (subject-object relationship) for adequate training and performance in the health area.